Experimental research and numerical simulations of a ceramic panel used for solar energy conversion. (December 2019) - Żukowski, Mirosław; Woroniak, Grzegorz; Piotrowska-Woroniak, Joanna
Highlights: Experimental research on ceramic panel carried out for the first time. Determination of the pressure drop of the fluid flowing through the collector. Determination of the thermal performance of ceramic solar panel. Development and positive validation of the ceramic CFD model. Abstract: The paper presents the results of the laboratory testing and numerical simulations of ceramic solar panels. The experimental research was carried out in artificial (laboratory) operating conditions. Rise in temperature and pressure drop of the fluid flowing through the collector was measured. As a result of the tests, the linear relationship between efficiency and reduced temperature difference was determined. While the pressure drop was approximated by the exponential function. Another research method based on numerical modelling using Computational Fluid Dynamics (CFD) algorithms was applied in this study. The three-dimensional geometric model of the ceramic panel was developed using the application included in the Ansys v. 19.2 package. The data obtained from computer simulations were compared with the results of the experiment to validate the numerical model. In order to find potential opportunities to increase the efficiency and due to the fact that the ceramic panel can be made in various inlet and outlet configurations, three simulation cases were considered: diagonal, top – bottom, and left – right. As the results of numerical calculations showed, the largest flow irregularity occurred in the last configuration. Based on the analysis of the test results, it can be concluded that, in spite of some disadvantages, ceramic panels can compete with traditional solar collectors currently available on the market.